The Effect Of Corporate Governance Mechanisms On The Valuation Of Comprehensive Income Reporting In Nigeria - Usman, Aliyu Baba; Amran, Noor Afza; Shaari, Hasnah (Universiti Utara Malaysia, 2017)
This study investigates the influence of corporate governance mechanisms on the valuation of other comprehensive income in Nigeria. The sample of this study consists of 327 firm-year observations comprising of 117 firms listed on the Nigerian Stock Exchange for the period of 2010 to 2014. The findings reveal that there is a positive influence of corporate governance mechanism on the investors’ pricing of other comprehensive income. Findings show that for firms with weak governance mechanisms, other comprehensive income is value relevant, but is more significantly priced for strong governance firms. This study finds a similar result when other comprehensive income interact with individual elements of corporate governance factor. Therefore, corporate governance mitigates reliability concerns associated with fair value earnings, agency cost will be minimised and investors are more likely to view other comprehensive income as more value relevant. It is therefore recommended that reporting entities should pursue best corporate governance practices in order to enhance investors’ confidence in the reliability of other comprehensive income.